(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines how social realities are reflected in the literary works of Erkin A’zam, a prominent figure in contemporary Uzbek literature. Through thematic and stylistic analysis of selected stories, this research explores the intersection of individual psychology and societal dynamics, revealing how A’zam’s minimalist yet poignant narratives serve as a critique of cultural and structural norms.